Lipid Update - Vinall, Maria (MD Conference Express, 2011)
Although the side effects that are associated with statin use are limited, the risk of adverse events becomes more significant as the dose increases when they are used in combination with other medications and in certain patient populations (pregnant women, the elderly, and children). This article discusses several of the at-risk populations and how to treat them.